2019
DOI: 10.1108/bij-07-2018-0219
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and workplace well-being: moderating role of sustainability practices

Abstract: Purpose How psychological variables especially self-efficacy plays significant role to attain workplace well-being is yet to be explained. The extant literature calls for further research works in the field of sustainability practices to bridge the gap between self-efficacy and workplace well-being. The purpose of this paper is to extend the literature of workplace well-being while scientifically examining the moderating role of sustainability practices. Design/methodology/approach The study collected data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 73 publications
2
94
0
Order By: Relevance
“…Work and life stress create pressure in the mind of employees, making them inefficient in thinking out of the box. To ensure sustainable practices and healthy work environment in the organization, self-efficacy is needed (Singh et al, 2019d). To increase efficiency and productivity of an employee, an effective leadership style is desirable (Turner and M€ uller, 2005).…”
Section: Literature Review and Hypothesis 21 Transformational Leadership And Employee Efficiencymentioning
confidence: 99%
“…Work and life stress create pressure in the mind of employees, making them inefficient in thinking out of the box. To ensure sustainable practices and healthy work environment in the organization, self-efficacy is needed (Singh et al, 2019d). To increase efficiency and productivity of an employee, an effective leadership style is desirable (Turner and M€ uller, 2005).…”
Section: Literature Review and Hypothesis 21 Transformational Leadership And Employee Efficiencymentioning
confidence: 99%
“…A person’s general self-efficacy is a stable, trait-like belief in his/her competence (Singh et al , 2019; Chen et al , 2001; Bandura, 1997). General self-efficacy is distinct from task-specific self-efficacy, which is a belief about one’s ability to perform a defined task.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Employee well-being is connected to various performance, for example, productivity, employee turnover, and work-life balance (Bakker and Oerlemans, 2011;Bozionelos and Singh, 2017;Deloitte, 2017;Keeman et al, 2017). Singh et al (2019a) indicated that the positive relationship between self-efficacy and workplace well-being (see also Singh et al, 2019b). Performance not only depends on both financial and non-financial support such as job autonomy and work-life balance.…”
Section: Literature Reviewmentioning
confidence: 99%